Clinical and mutational spectrum of Japanese patients with Charcot‐Marie‐Tooth disease caused by GDAP1 variants. Issue 3 (19th April 2017) - Yoshimura, A.; Yuan, J.‐H.; Hashiguchi, A.; Hiramatsu, Y.; Ando, M.; Higuchi, Y.; Nakamura, T.; Okamoto, Y.; Matsumura, K.; Hamano, T.; Sawaura, N.; Shimatani, Y.; et al.
Abstract : Background: Mutations in GDAP1 are responsible for heterogeneous clinical and electrophysiological phenotypes of Charcot‐Marie‐Tooth disease (CMT), with autosomal dominant or recessive inheritance pattern. The aim of this study is to identify the clinical and mutational spectrum of CMT patients with GDAP1 variants in Japan. Materials and Methods: From April 2007 to October 2014, using three state‐of‐art technologies, we conducted gene panel sequencing in a cohort of 1, 030 patients with inherited peripheral neuropathies (IPNs), and 398 mutation‐negative cases were further analyzed with whole‐exome sequencing. Results: We identified GDAP1 variants from 10 patients clinically diagnosed with CMT. The most frequent recessive variant in our cohort (5/10), c.740C>T (p.A247V), was verified to be associated with a founder event. We also detected three novel likely pathogenic variants: c.928C>T (p.R310W) and c.546delA (p.E183Kfs*23) in Case 2 and c.376G>A (p.E126K) in Case 8. Nerve conduction study or sural nerve biopsy of all 10 patients indicated axonal type peripheral neuropathy. Conclusion: We identified GDAP1 variants in approximately 1% of our cohort with IPNs, and established a founder mutation in half of these patients. Our study originally described the mutational spectrum and clinical features of GDAP1 ‐related CMT patients in Japan. Abstract :